1905 Pa. Laws 252-53, No. 180, § 8 - (:unkn) unknown (My University, 1905)
No person shall make use of what is known as buckshot in hunting deer or fawn within this Commonwealth, or shall kill or wound, or attempt to kill or wound, any deer or fawn within this Commonwealth, or shall kill or wound, or attempt to kill or wound, any deer or fawn within this Commonwealth by or with or through the use of a gun propelling or emitting more than one pellet, bullet or ball at a single discharge; and persons violating this provision shall be subject to the penalties provided by existing law for the unlawful taking or killing of deer or fawn.
Keywords: HUNTING REGULATION